Impact of micro factors on women career development in Nigeria hotels - Ebere, Ihemeje Josephine (International Organization Of Scientific Research, 2016)
This article examined the impact of micro factor on the career development of women in hotel industry in Etsako West LGA of Edo State. About 460 women in 18 selected hotels in Etsako West LGA were sampled using questionnaire. Multiple regression analysis was applied to analyse the data collected. The results shows that all the dimensions of micro factor; organisational culture (r = 0.185; p <.05), family factor (r = 0.306; p < .05) and individual factor (r =0.381; p < .05) has a significant relationship on career development of women in the studied hotels in Etsako West LGA. Regarding the strength of the relationship, the results shows that the organisational culture has small but positive relationship, family factor have a positive but medium relationship, and the individual factor have a positive, but medium relationship. Results of the micro factor dimensions that contributed to the prediction of the career development of women in hotel industry in Etsako West LGA shows that organizational factor made the highest contribution to career development and as well significant (β=0.756; p<.05), followed by family factor which is also significant (β= 0.182; p<.05). Individual factor made the lowest contribution but significant (β= 0.133; p<.05). To this end, this implies that if organizational culture is not favourable, it could have effect on the career development opportunities given to women, thereby influencing the number of women progressing to higher management positions in hotel industry. This suggests that managers of hotel industry should put in place gender friendly organisational policies that could encourage professionalism, including, enforcement of family support programmes that could enhance the career path of women. In view of this, favourable organisation policy, complimented with family support can enhance career development of women in hotel industry. Hence, managers of hotel industry should put in place gender friendly organisational policies that could encourage professionalism and merit rather than discrimination. This will ensure that women who show the required individual skills, competence, and experience could attain their target career aspiration unobstructed.